Environmental Management System for Small- and Medium-sized Enterprises: Japan’s Eco-Action 21 Guidelines - Toshihiko, Goto (2016)
Ⅰ. Needs for Environmental Management Ⅱ. Eco-Action 21 Ⅲ. Overview of Certification & Registration System